The Federal Democratic Republic of Ethiopia : Poverty Reduction Strategy Paper Growth and Transformation Plan 2010/11-2014/15: Volume II. (IMF Staff Country Reports; Country Report ;, 2011)
This strategic paper discusses Ethiopia's growth and transformation plan (GTP) for the periods 2010/2011 and 2014/2015. The basis for the GTP has been the policy matrix, which is the benchmark placed in the government's existing Welfare Monitoring and Evaluation (M and E) System since 1996. The M and E system provides the government with reliable mechanisms to measure the efficiency of those government actions and the effectiveness of public policies in achieving the objectives stated in the GTP. The paper discusses the structure and legal framework of the policy matrix.